Perlindungan Hukum Terhadap Korban Kekerasan Seksual Sesama Jenis Dihubungkan dengan Tujuan Pendidikan Pesantren - Akbar Ramdani, Ilham; Farrih Izadi, Fariz (Adagium: Jurnal Ilmiah Hukum, 2025)
This research aims to determine and analyze the legal responsibility of Pesantren that ignore victims of homosexual violence in Pesantren in relation to legal protection for victims of homosexual violence in Pesantren in relation to the educational goals of Pesantren. The research method used is a normative juridical approach with qualitative methods to produce descriptive-analytical data. This research resulted in the conclusion that the Pesantren neglect of victims of homosexual violence is a violation that can be subject to administrative sanctions. However, the regulations that accommodate legal protection do not explain the mechanism for providing sanctions and categorizing the level of violations, giving rise to legal uncertainty. Legal protection for victims of homosexual violence in Pesantren is related to the educational goals of Pesantren; a) preventing sexual violence through the formation of superior individuals; b) preventing sexual violence by improving the quality of life of the community; c) development of Islamic values rahmatan lil 'alamin; d) the implementation of Pesantren based on national law.